Report on the 1st International Workshop of the IUGS Lower Cretaceous Ammonite Working Group, the 'Kilian Group' (Lyon, 11 July 2002) - Hoedemaeker, Philip J. (2003)
The Lower Cretaceous Ammonite Working Group forms part of the IUGS Subcommission on Cretaceous Stratigraphy (Peter Rawson, chair) and is the successor of the Lower Cretaceous Cephalopod Team that formed part of IGCP Projects 262 and 362 respectively. The latter team had organized five Workshops (Klein & Hoedemaeker, 1999;Hoedemaeker & Rawson, 2000) and this is the first workshop under the new IUGS umbrella, which was organized by Stéphane Reboulet (Université de Lyon 1) directly after the 3rd French Symposium on Stratigraphy (Lyon, 8–10 July 2002). The workshop was attended by 18 members from 13 countries. The attendants agreed to call the group the ‘Kilian Group' after the famous French palaeontologist W. Kilian.